2006
DOI: 10.1097/01.gme.0000227400.60816.52
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intranasal 17β-estradiol administration on serum bioactive interleukin-6 and C-reactive protein levels in healthy postmenopausal women

Abstract: The results of our study show that intranasal, similarly to transdermal, E2 administration does not increase serum CRP levels in postmenopausal women. They also support the hypothesis that CRP increase during oral estrogen treatment is not mediated by the enhancement of interleukin-6 production by the immune cells but is rather caused by the hepatic first-pass metabolism effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
153
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(163 citation statements)
references
References 43 publications
8
153
0
2
Order By: Relevance
“…The findings of the present study are consistent with other studies that have shown that the side-effect profile of the testosterone patch appears to be acceptable to women receiving estrogen treatment and those who have undergone natural menopause and are taking estrogens with a progestin, as well as those being treated with testosterone alone (17,19,20,22). Although the evidence of the potential benefit of testosterone treatment in women suffering from HSDD is very convincing, there has been a lack of such data for treatment options in transsexual women.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of the present study are consistent with other studies that have shown that the side-effect profile of the testosterone patch appears to be acceptable to women receiving estrogen treatment and those who have undergone natural menopause and are taking estrogens with a progestin, as well as those being treated with testosterone alone (17,19,20,22). Although the evidence of the potential benefit of testosterone treatment in women suffering from HSDD is very convincing, there has been a lack of such data for treatment options in transsexual women.…”
Section: Discussionsupporting
confidence: 91%
“…In some studies, statistically significant correlations have been observed between changes in sexual desire and testosterone serum concentrations after treatment with a testosterone patch (13, 14). Women suffering from low libido in the natural menopause may also benefit from testosterone treatment while taking estrogens (20,21) or not taking estrogens (22). Some transsexual women wish to receive treatment with a progestational compound, as they believe that addition of this female hormone will bolster the feminization process, but there is no evidence in support of this contention (23).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental data suggest direct effects of testosterone on body composition, lipid levels and glucose metabolism. We postulate that increased androgenicity contributes to the accumulation of visceral fat and impairment of glucose metabolism, creating a vicious circle, whereby the increase in insulin and fat tissue in turn promote the production of 123 Surgical T Transdermal (patch) 300 mg per day 24 weeksBraunstein et al 124 Surgical T Transdermal (patch) 150/300/450 mg per day 24 weeksSimon et al 125 Surgical T Transdermal (patch) 300 mg per day 24 weeksDavis et al 126 Surgical T Transdermal (patch) 300 mg per day 24 weeksShifren et al 120 Natural T Transdermal (patch) 300 mg per day 24 weeksNathorst-Boost et al 127 Natural T Transdermal (gel) 10 mg per day 3 monthsBurger et al 128 Natural/surgical T Implant 50 mg  1 6 weeks -Davis et al 122 Natural/surgical T Implant 50 mg per 3 months 24 months k fat mass Farish et al 129 Surgical T Implant 100 mg  1 6 monthsHickok et al 130 -MT Oral 1.25 mg per day 6 months k HDL-C Watts et al 131 Surgical MT Oral 2.5 mg per day 24 months k HDL-C, triglycerides Basaria et al 132 Natural/surgical MT Oral 2.5 mg per day 16 weeks k HDL-C, triglycerides m fibrinogen Dobs et al 133 Natural/surgical MT Oral 2.5 mg per day 16 weeks k HDL-C, triglycerides, fat mass Lobo et al 134 Natural/surgical MT Oral 1.25 mg per day 16 weeks k HDL-C, triglycerides Warnock et al 135 Surgical MT Oral 1.25 mg per day 8 weeks k HDL-C, triglycerides Leao et al 136 Surgical MT Oral 1.25 mg per day 12 months k HDL-C m visceral fat mass Barrett-Connor et al 137 Surgical MT Oral 1.25 mg per day 24 months k HDL-C, triglycerides Raisz et al 138 Natural/surgical MT Oral 2.5 mg per day 9 weeks k HDL-C, triglycerides Penotti et al 139 Natural TU Oral 40 mg per day 8 months k HDL-C, m pulsatile index (PI)…”
Section: Discussionmentioning
confidence: 99%
“…In several studies addition of testosterone to estrogen therapy has been reported to improve sexual function and well-being. 120,121 In addition, beneficial effects on bone mineral density have been observed. 122 Despite the large number of studies investigating the effects of testosterone coadministration, there are limited long-term data regarding the cardiovascular safety of this combination therapy.…”
Section: Postmenopausal Testosterone Therapymentioning
confidence: 99%
“…Low-dose testosterone supplementation improved functional capacity, insulin sensitivity and muscle strength in elderly female patients with chronic heart failure, and no androgenic side effects were detected (Iellamo et al 2010). In several studies, addition of testosterone to estrogen therapy has been reported to improve sexual function and well-being in naturally and surgically menopausal women (Shifren et al 2006). These findings prompted us to postulate that addition of physiological dose of testosterone to estrogen therapy may confer cardioprotection by direct action on the myocardium.…”
Section: Introductionmentioning
confidence: 99%